Use of solid phase extraction for the sequential injection determination of alkaline phosphatase activity in dynamic water systems - Santos, Inês C. (2013)
In this work, a solid phase extraction sequential injection methodology for the determination of alkaline phosphatase activity in dynamic water systems was developed. The determination of the enzymatic activity was based on the spectrophotometric detection of a coloured product, p-nitrophenol, at 405 nm. The p-nitrophenol is the product of the catalytic decomposition of p-nitrophenyl phosphate, a noncoloured substrate. Considering the low levels expected in natural waters and exploiting the fact of alkaline phosphatase being a metalloprotein, the enzyme was pre-concentrated in-line using a NTA Superflow resin charged with Zn2þ ions. The developed sequential injection method enabled a quantification range of 0.044–0.441 unit mL 1 of enzyme activity with a detection limit of 0.0082 unit mL 1 enzyme activity (1.9 mmol L 1 of pNP) and a determination rate of 17 h 1. Recovery tests confirmed the accuracy of the developed sequential injection method and it was effectively applied to different natural waters and to plant root extracts.